The League of Extraordinary Gentlemen [videorecording (DVD)] - Norrington, Stephen, 1964-; Connery, Sean; Shah, Naseeruddin; Wilson, Peta, 1970-; Curran, Tony, 1969-; Townsend, Stuart, 1972-; Flemyng, Jason; Ryan, Max, 1967-; West, Shane; Goodman-Hill, Tom (20th Century Fox Home Entertainment, 2003)
A legion of superheroes, the likes of which mankind had never seen, must band together under the leadership of Allan Quatermain to save the world from "The Fantom" who is threatening to launch a global Armageddon.